Pengembangan Modul Pembelajaran Elektronik Berbasis E-Learning Dengan Aplikasi Edmodo Dalam Mata Pelajaran Dasar Listrik dan Elektronika Kelas X Teknik Instalasi Tenaga Listrik di SMK Negeri 34 Jakarta - Yusuf Fadhilah; Mochammad Djaohar; Aris Sunawar (Journal of Electrical Vocational Education and Technology, 2020)
ABSTRACT This research and development is to determine the feasibility of instructional media and produce electronic learning modules based on e-learning with Edmodo applications in Basic Electric and Electronic subjects as learning support media. This research was held in SMK Negeri 34 Jakarta with a sample of 34 people using the Research and Development (R&D) research method with the ADDIE development model which only reached the Implementation stage. The research instrument used a questionnaire as an assessment sheet given to material experts, instructional media experts, and students. Data obtained through testing in the form of pre-test, post-test, and questionnaires are processed qualitative and quantitative. The results of this study indicate: 1) Analysis, the results of the needs analysis require learning support media for the learning support process, and the results of the competency analysis that the subjects of Basic Electricity and Electronics are suitable for use in research. 2) Design, the results of learning pattern design resulting the conducting research and the result of module making producing 11 different modules in odd semester of Basic Electricity and Electronics subject. 3) Development, produce learning media in the form of e-learning based electronic learning modules with edmodo applications in Basic Electric and Electronics subjects that have met the very feasible criteria with the results obtained: 1. Material expert assessment gets a percentage of 93.75% (Very Feasible); 2. Assessment of instructional media experts get a percentage of 71.25% (Feasible). 4) Implementation, trial use of the product to get a percentage of product eligibility to get a percentage value of 84% (Very Feasible) and produce test scores in the form of pre-test and post-test as follows: The results of the experimental class assessment, obtained the average total value of the electrical materials section in the pre-test 37 and post-test 70, while from the sub-section of the electric current circuit, the average value of the total pre-test is 40 and the post-test is 75. In the control class assessment results, obtained the average total value of the electrical materials section in the pre-test of 45 and post-test of 56, while from the direct current electric section subsection the total average value at the pre-test is 54 and the post-test is 68. Based on these results, the development of this study is very feasible to be used as a learning support media that provides a significant increase in value in the experimental class. ABSTRAK Penelitian dan pengembangan ini untuk mengetahui kelayakan media pembelajaran dan menghasilkan modul pembelajaran elektronik berbasis e-learning dengan aplikasi edmodo dalam mata Dasar Listrik dan Elektronika sebagai media penunjang pembelajaran. Penelitian dilaksanakan di SMK Negeri 34 Jakarta dengan jumlah sampel 34 orang menggunakan metode penelitian Research and Development (R&D) dengan model pengembangan ADDIE yang hanya sampai tahap Implementasi. Instrumen penelitian menggunakan angket sebagai lembar penilaian yang diberikan kepada ahli materi, ahli media pembelajaran, dan peserta didik. Data didapat melalui pengujian berupa pre-test dan post-test serta angket yang diolah secara kualitatif dan kuantitatif. Hasil dari penelitian ini menunjukkan: 1) Analysis, hasil dari analisis kebutuhan membutuhkan media pendukung pembelajaran untuk proses penunjang pembelajaran, dan hasil dari analisis kompetensi bahwa mata pelajaran Dasar Listrik dan Elektronika sesuai digunakan dalam penelitian. 2) Design, hasil perancangan pola pembelajaran menghasilkan proses pelaksanaan penelitian dan hasil penyusunan modul menghasilkan 11 modul berbeda dalam semester ganjil mata pelajaran Dasar Listrik dan Elektronika. 3) Development, menghasilkan media pembelajaran berupa modul pembelajaran elektronik berbasis e-learning dengan aplikasi edmodo dalam mata pelajaran Dasar Listrik dan Elektronika yang telah memenuhi kriteria sangat layak dengan hasil yang didapat: 1. Penilaian ahli materi mendapatkan nilai persentase sebesar 93,75% (Sangat Layak); 2. Penilaian ahli media pembelajaran mendapat nilai persentase sebesar 71,25% (Layak). 4) Implementation, uji coba pemakaian produk untuk mendapatkan hasil persentase kelayakan produk memperoleh nilai persentase sebesar 84% (Sangat Layak) dan menghasilkan nilai dari pengujian berupa pre-test dan post-test sebagai berikut: Hasil penilaian kelas eksperimen, memperoleh nilai rata-rata total dari subbab bahan-bahan listrik pada pre-test sebesar 37 dan post-test sebesar 70. Sedangkan dari subbab rangkaian listrik arus searah memperoleh nilai rata-rata total pada pre-test sebesar 40 dan post-test sebesar 75. Pada hasil penilaian kelas kontrol, memperoleh nilai rata-rata total dari subbab bahan-bahan listrik pada pre-test sebesar 45 dan post-test sebesar 56. Sedangkan dari subbab rangkaian listrik arus searah memperoleh nilai rata-rata total pada pre-test sebesar 54 dan post-test sebesar 68. Berdasarkan hasil tersebut, pengembangan pada penelitian ini sangat layak digunakan sebagai media penunjang pembelajaran yang memberikan peningkatan nilai yang signifikan pada kelas eksperimen.